Penerapan Undang-Undang Tentang Pemilihan Umum Dalam Upaya Pemenuhan Hak Pilih Penyandang Disabilitas di Desa Bola - Muharawati; Ismail Ali; Mustafa, Dewi Wahyuni; Mustari; Andi Herawati (YP-SDI Lamaddukelleng, 2025)
The purpose of the study was to determine the implementation of the right to vote for people with disabilities in the 2024 general election based on Law Number 7 of 2017 concerning General Elections. The data collection method used was primary legal materials with interviews and secondary legal materials, namely other legal literature and official archives. The results of this study indicate that the factors that hinder the implementation of the right to vote for people with disabilities in Bola Village, Bola District, Wajo Regency are 1) there is still data that is not synchronized and concrete between the Wajo Regency KPU and the Wajo Regency Social Service regarding data on people with disabilities in Wajo Regency, 2) Socialization related to elections for people with disabilities is not evenly distributed, 3) PPS still does not understand the provision of assistance services to people with disabilities, so they are considered less friendly by voters with disabilities, 4) There are still people who are less able to accept differences and have not been able to act inclusively towards people with disabilities, 5) Rejection of families of people with disabilities who do not want to be registered